Mother-daughter communication of sexual and reproductive health (SRH) matters and associated factors among sinhalese adolescent girls aged 14-19 years, in Sri Lanka - D. Mataraarachchi; Pathirana T.E. A; Mahesh Buddhika P.K; Vithana P.V.S. C (BMC, 2023)
Abstract Introduction School-based and community-based sexuality education has not shown a significant impact on the sexual and reproductive health (SRH) outcomes of Sri Lankan adolescents. Parents, as the primary educators of adolescents, could potentially serve as better sources for providing individualized sexuality education to their children. Objective To assess the sexual and reproductive health (SRH) topics discussed between mothers and daughters, barriers to communication, and associations of SRH communication among Sinhala adolescent girls aged 14-19 years in Sri Lanka. Methods A descriptive cross-sectional study was conducted among a sample of 810 Sinhala adolescent girls using a pre-tested, self-administered questionnaire. Descriptive statistics pertaining to mother-daughter communication in SRH matters were presented using frequencies and percentages. Bivariate analysis was performed to evaluate the association of selected socio-demographic factors with mother-daughter SRH communication, while binary logistic analysis was used to assess the independent association of chosen demographic factors with mother-daughter SRH communication. Results The majority of the respondents (67.1%, n = 540) indicated a willingness to discuss SRH matters with their mothers. For 78.2% (n = 632) of the respondents, the mother was the preferred source of SRH information. Common topics discussed between the mothers and daughters included issues related to menstruation (88.4%, n = 701) and maintaining personal boundaries (94%, n = 718), whereas less discussed topics included homosexuality (21%, n = 166), and preventing unwanted pregnancy (38.6%, n = 305). Cultural barriers, fear of mothers' reactions, and mothers' lack of confidence in responding to their daughter's SRH matters were the main barriers to discussing SRH topics with mothers. Adolescent girls' age, and family income level were significantly associated with mother-daughter SRH communication. Conclusions and recommendations Although a majority of adolescent girls preferred to share their sexual health concerns with their mothers, a notable barrier was the lack of confidence from the mother's side. Furthermore, the scope of mother-daughter sexual communication in this study was largely limited to less sensitive topics. In light of these findings, it is suggested that interventions targeted at parents be developed alongside school-based sex education for adolescents. These interventions should aim to enhance parents' knowledge and skills in discussing sexual health matters with their adolescent children.